EP676 Outcomes after conservative treatment of stade II and III serous borderline tumors of the ovary. (1st November 2019) - Maria, S; Maulard, A; Genestie, C; Pautier, P; Bentivegna, E; Leary, A; Chargari, C; Morice, P; Gouy, S
Abstract : Introduction/Background: The aim of this study was to assess the outcomes of the largest series of conservative treatment for advanced stages serous borderline ovarian tumor. Methodology: Between 1973 and 2017, 65 patients were treated conservatively for an advanced-stage serous borderline ovarian tumor. Patient outcomes were reviewed. Results: 28 patients had undergone a unilateral salpingo-oophorectomy, 12 a unilateral cystectomy and 25 unilateral salpingo-oophorectomy and controlateral cystectomy. Eight patients had invasive implants. The median duration of follow-up was 73 months (range, 12–369). The recurrence rate was high (58%). Eight recurrences were observed under the form of invasive disease: 2 (25%) and 6 (11%) in patients having initially respectively invasive implants and noninvasive implants. Three deaths had occurred, all of them in patients with noninvasive implants and micropapillary patterns (2 of them having a complete resection of peritoneal implants). Twenty-four pregnancies (13 spontaneous) were observed in 29 patients wishing to be pregnant. Seven patients had secondary infertility. Conclusion: This study demonstrates that the conservative treatment of advanced stage borderline ovarian tumors (with noninvasive implant) can be achieved to preserve the possibility of pregnancy but the recurrence rate is high. Nevertheless, three deaths were observed, all of them concerning patients with noninvasive implants and micropapillary patterns. Initial presence of invasive implant doesn't seem to impact significantly the risk of recurrence under the form of invasive disease. This important data should be shared with such patient when a conservative approach is discussed. A careful follow-up should be done in this subgroup of patients. Disclosure: Nothing to disclose.